THU0360 Interferon-gamma release assays in rheumatic patients: Baseline study and in the course of anti-tumor necrosis factor-alpha agents. (23rd January 2014) - Martínez-Morillo, M.; Mínguez, S.; Mateo, L.; Latorre, I.; Domínguez, J.; Grados, D.; Tejera, B.; Riveros, A.; Holgado, S.; Olivé, A.; Tena, X.
Abstract : Background: IFN-γ release assays are useful methods for diagnosing LTBI (latent tuberculosis infection). It allow us to detect: a) false negative TST in anergic subjects, b) false positives in BCG-vaccinated patients and c) NTM (non-tuberculous mycobacterias) previously sensitized individuals. All in all, these tests contribute to detect additional cases of LTBI. Objectives: To establish the usefulness of blood interferon-γ (IFN-γ) release assays in patients with inflammatory rheumatic diseases scheduled for anti-TNF-α treatment and at the follow up. Methods: Prospective study including rheumatic patients starting an anti-TNF-α agent. All patients underwent TST (two step), a chest radiograph, QuantiFERON GOLD in tube (QFN-G-IT), and T-SPOT.TB. Both tests were repeated after a year of anti-TNF treatment in 21 patients. As control group, 35 adult individuals were included. Concordance were analyzed by Cohen's kappa test. Results: We included 53 patients (18 male/35 female) candidates for anti-TNF-α (18 rheumatoid arthritis, 13 ankylosing spondylitis, 9 psoriatic arthritis and 13 miscellanea). Mean age was 49±13 years and mean disease evolution was 8.8±8 years. Twenty-four out of 53 patients (45.3%) were receiving systemic steroids, mean daily dose 9.1±11.9 mg/day. BCG vaccination status was documented in 3 patients, 2 referred history suggestive of TB disease and other 3 patients had contact with a confirmed TB case in the past. The results of our study are summarized in Table 1 . The differences in the results between the IFN-γ tests were not significant ( p= 0.675). Interestingly enough, neither T-SPOT.TB nor QFN-G-IT were significant in comparison to TST results ( p= 0.344 and p= 0.727, respectively). Overall agreement between TST and T-SPOT.TB and QFN-G-IT was 77.35% (k=0.33; and k=0.40, respectively), and between both in vitro tests was 83.01% (k=0.57) was observed. Three patients with positive TST and negative T-SPOT.TB and QFN-G-IT, was positive on ELISPOT after stimulation with NTM sensitins. Positive TST, T-SPOT.TB and QFN-G-IT results were not affected by the immunosuppressive therapies. We found 4 conversions (1 patient convert T-SPOT and QFN, and 3 patients convert only T-POT) out of 21 cases evaluated after a year under anti-TNF-α agents. We also observed 2 reversions, one in a patient who had undergone prophylactic treatment for tuberculosis. Conclusions: In those patients with a high risk of developing active TB, the combined use of TST and IFN-γ may be recommended to increase the overall number of LTBI diagnosis. Reversion is described in subjects who have made prophylaxis. More studies are needed to recommend prophylaxis in conversions. Disclosure of Interest: None Declared